Online at risk! Online activities of children in dormitories: Experiences in a Croatian County - Vejmelka, Lucija; Matković, Roberta; Borković, Davorka (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2020)
The virtual environment available through the internet is an important domain of children’s subjective well-being. Widespread usage of information technology brings risks as well as benefits, a topic now under intensive study by professionals in multiple fields. To date there has been a lack of research about the experiences of children from group accommodation settings when navigating the virtual environment. The main goal of the present study, which involved 510 high school students living in dormitories in Split-Dalmatia County, was to determine and document patterns of internet usage and internet addiction, and to examine another internet behavior, cyberbullying. Our results show that 3.73% of the children we studied manifested a severe level of internet addiction, while about one third took part in cyberbullying as victim, perpetrator, or both. An important finding is that children involved with cyberbullying have significantly higher levels of internet addiction, suggesting a relationship between these phenomena. In the second, qualitative, phase of the study, the quantitative research findings were discussed with children, parents, teachers, and staff. Our results enable a better understanding of young people`s behaviors in the online world, and could contribute to the development of educational programs for children and young people and the promotion of evidence-based practice in dormitory settings.